Harry Potter and the prisoner of Azkaban - Rowling, J. K.; Dale, Jim. (New York : Bloomsbury, 1999)
"For twelve years, the dread fortress of Azkaban held an infamous prisoner named Sirius Black. Convicted of killing thirteen people with a single curse, he was said to be the heir apparent to the Dark Lord, Voldemort. Now he has escaped, leaving only two clues as to where he might be headed: Harry Potter's defeat of You-Know-Who was Black's downfall as well. And the Azkaban guards heard Black muttering in his sleep, "He's at Hogwarts." Harry Potter isn't safe, not even within the walls of his magical school, surrounded by his friends. Because on top of it all, there may well be a traitor in their midst"--Container.
Unabridged.
Compact discs.
Statement of responsibility from container.
Third in the Harry Potter series.
Read by Jim Dale.
Keywords: Potter, Harry (Fictitious character) -- Juvenile fiction; Hogwarts School of Witchcraft and Wizardry (Imaginary organization) -- Juvenile fiction; Wizards -- Juvenile fiction; Magic -- Juvenile fiction; Schools -- Juvenile fiction; Wizards -- Fiction; Magic -- Fiction; Schools -- Fiction; England -- Juvenile fiction; England -- Fiction